Water flows generating hysteresis on the S-shape. Issue 1 (June 2021) - Nichele, S; Bayle, S; Vaillant, Y; Janson, E; Guillaume, R; Houdeline, JB
Abstract: For a given hydraulic design and a given guide vane opening, pump-turbine S-shape description in the turbine quadrant can be different depending on whether measurements are performed from the high discharge to the low discharge area or vice versa. A specific device for visualizing the flow field inside the runner has been developed in a scaled model of a medium head pump turbine machine in order to analyze and understand this hysteresis phenomenon. Windows, lights, high-resolution cameras and tracers have been combined to visualize the flow field. Flow field behavior has been studied in the runner and in the vaneless area located between the guide vanes and the runner. Two different methods of analyzing the flow field in the runner have been tested. Depending on the localization of the operating points and the direction of the S-shape description, different flow structures have been directly observed. In parallel, a study of the impact of this hysteresis on transient behavior in turbine mode has been carried out. Understanding this phenomenon is important to improve future design and to accurately measure the S-shape during model tests.